Current situation and measures proposed in managing teaching capacity training activities for secondary school teachers in Phu Tho town, Phu Tho province under the orientation of renovating the general education curriculum - Nghiem, Thi Duong (Đại học Quốc gia Hà Nội, 2020)
Managing teaching and learning activities for teachers is an important task in general schools, especially in the context of renovating the current educational program. The paper presents the results of studying the situation of teaching capacity training activities management for secondary school teachers in PhuTho town, PhuTho province under the orientation of renovating the general education curriculum, and on that basis, proposes a number of management measures to improve teaching capacity for teachers to meet the current requirements of educational innovation.